Responding to the child’s need for the father’s presence through Sri Lankan labor law - Wijeyesekera, R. (University of Colombo, 2025)
The world of work is not devoid of parent-child relationships and corresponding obligations. Legal systems around the world responds to these human needs by recognizing, inter alia, parental leave’ entitlements of employees. Based on different grounds unique to each legal system, such leave is communicated as ‘maternity’, ‘paternity’ or ‘parental’. Sri Lanka mandates ‘maternity leave’ female employees at an optimal level for both the public and private sectors, enabling recovery after childbirth, maternity care during pre-and post-natal periods, including the facilitation of breast-feeding. Yet, only very nominal paternity leave is granted to male employees. Among the many signals this nominal paternity leave sends, such as entrenching gender norms and stereotypes relating to childcare, it undermines the child-father relationship denying both their rights as a child and as a father. This shows the law’s reluctance to recognize the importance of fatherhood and paternal care during the early stages of a child’s life, at a similar weight it attaches to motherhood and maternal care. This denies Sri Lankan children their father’s active involvement in their early life, while discriminating against fathers employed in state and private sectors. At a significant juncture where the country is gearing towards reviewing the existing employment laws with a view to introducing a comprehensive Labor Code, this paper argues for enhanced legal provision for paternity leave through a comparative analysis of the legal framework of neighboring India. A doctrinal method is used to draw insights from Indian law and jurisprudence where paternity leave has been rationalized from a child rights perspective. International standards and comparative law are used as benchmarks to ensure enhanced consistency with the best interests of every child without discriminating based on the legal status of the parent-child relationship. The paper recommends legal and institutional reforms that ensure the best interests of Sri Lankan children by duly accommodating fatherhood in the Sri Lankan world of work.
Keywords: Paternity leave; Child rights; Employment law